2014
DOI: 10.1186/1471-2458-14-64
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of condom use by men who have sex with men before and after the Avahan intervention in Andhra Pradesh state of India

Abstract: BackgroundTwo rounds of integrated biological and behavioural assessment (IBBA) surveys were done among men who have sex with men (MSM) in Andhra Pradesh during 2006 and 2009. Avahan, the India AIDS initiative, funded by the Bill and Melinda Gates Foundation implemented HIV prevention interventions among MSM starting around the time of the first round of IBBA.MethodsData on socio-demographic, sex behaviour characteristics and HIV status of MSM from the two IBBA rounds were used. Changes in the rates of consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
(15 reference statements)
2
7
0
Order By: Relevance
“…Correlates of prevalent HIV are also consistent with reports from India[18-20,23,26-28]. Being married remained consistently associated with a higher likelihood of being HIV-infected even in smaller cities.…”
Section: Discussionsupporting
confidence: 88%
“…Correlates of prevalent HIV are also consistent with reports from India[18-20,23,26-28]. Being married remained consistently associated with a higher likelihood of being HIV-infected even in smaller cities.…”
Section: Discussionsupporting
confidence: 88%
“…These findings are consistent with other studies conducted in various countries globally. For example, similar findings were observed among MSM in Andhra Pradesh, Maharashtra and Tamil Nadu in India where HIV prevention programme had a positive impact on increasing condom use [45][46][47] as was the case in Anhui and Sichuan Provinces in China [48,49] and in Senegal [50].…”
Section: Plos Onesupporting
confidence: 68%
“…This finding is inconsistent with a study conducted in India [ 22 ] but supported by other studies conducted in China, which showed that condomless sex among MSM was more likely to occur when regular partners were involved [ 42 44 ]. The potential reasons for this include that MSM have a higher awareness of self-protection when having sex with casual partners [ 45 ], and using a condom with regular partners would be considered as an insult to the partner [ 39 ]. Even like this, previous studies indicated that a large proportion of Chinese MSM persistently engaged in condomless sex with casual partners [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%